Intervensi Superstisi terhadap Perspektif Adab bagi Masyarakat Minangkabau - Ridha Hasnul Ulya (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
Superstition and adab are among the many local pearls of wisdom in Minangkabau. Superstition is a statement that contains a supernatural meaning while adab is a condition that describes someone's unethical behavior. Contextually, there is a relationship between superstition and adab. The superstition that is formed in the life of the Minangkabau people is reconstructed from a civilization. The purpose of this paper is to describe and prove this relationship so that a common thread can be drawn regarding the relationship between superstition and Minangkabau people's manners. This research approach uses a qualitative approach. This study uses categorization techniques to reveal and interpret the data that has been collected. The data in question are the superstitions of the Minangkabau people which are reflected in adab, namely the manners of sitting, standing, walking, and behaving. Therefore, it is important to carry out an in-depth study to reveal the presence of superstitious interventions in Minangkabau society from the perspective of adab formation